Isolation and genomic characterization of the plant growth-promoting rhizobacterium GZY0 and its biocontrol potential against soft rot in Amorphophallus konjac - Zhong, Yu; Wu, Juan; Ren, Zhen; Wu, Cheng; Qian, Yingying; Wang, Luoping; Chen, Xu; Niu, Lisha; Tang, Zuoxin; Zhang, Yuyu; Wang, Yanhong; Xia, Tiyuan (Frontiers in Microbiology, 2025)
Bacterial soft rot is a destructive disease that hinders the production of Amorphophallus konjac. In this study, a bacterial strain (GZY0) antagonistic to Pectobacterium aroidearum was isolated from the rhizospheric soil of A. konjac using the solid agar plate confrontation test. Through 16S rRNA sequencing, gyrA gene sequencing, and ANI analysis, this GZY0 strain was identified as Bacillus velezensis. The cell suspension and cell-free supernatant of GZY0 produced bacteriostatic inhibition zones with diameters of 15.63 and 16.70 mm, respectively, against P. aroidearum. Both in vitro antagonist assays and greenhouse pot experiments demonstrated that GZY0 is effective at controlling soft rot in A. konjac. During in vitro antagonistic tests in A. konjac tissues, mixed inoculation with the cell suspension or cell-free supernatant of GZY0 provided control efficacy of 47.56% and 45.79%, respectively, compared with the inoculation of a P. aroidearum bacterial suspension alone. Greenhouse pot experiments further validated its disease-preventing potential, the disease index of the GZY0 + P. aroidearum-coinoculated group was 45.81% lower than that of the P. aroidearum-inoculatedgroup. Additional functional studies revealed that strain GZY0 exhibits excellent plant growth-promoting properties and capable of producing phosphorus-solubilizing zones on both inorganic and organic phosphorus media, with diameters of 11.68 mm and 7.50 mm, respectively. On CAS iron-supplemented medium, GZY0 produces an orange-yellow halo with a diameter of 11.33 mm and an A/Ar ratio of 1.19. Furthermore, GZY0 turns Salkowski reagent red, with an IAA yield of 17.77 mg/L. Furthermore, GZY0 exhibited antagonistic effects against Botryosphaeria dothidea, Fusarium oxysporum, F. solani, F. oxysporum f. sp. panax, and Colletotrichum gloeosporioides. Whole-genome sequencing demonstrated that the genome length of GZY0 was 4053804 bp and included 3,934 coding genes. In order to elucidate the biocontrol mechanisms of strain GZY0, genes related to nitrogen fixation, phosphorus solubilization, and IAA and siderophore production were identified, and 12 antagonism-related secondary metabolite synthesis gene clusters and induced systemic resistance-related genes were predicted. A total of 5,169 pan-genes were detected in the comparative genome, all possessing open pan-genes and closed core genes. Additionally, 3,240 homologous genes were shared among the six Bacillus spp. strains, with GZY0 harboring 171 unique homologous genes. In summary, our findings demonstrated that GZY0 exhibits plant growth promotion capabilities and serves as a potential biocontrol agent for soft rot in A. konjac. Hence, this strain warrants further development and application.